2018
DOI: 10.4103/1735-3327.226528
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin expression in gingival tissues of chronic periodontitis and aggressive periodontitis patients: An immunohistochemical analysis

Abstract: Background:Visfatin, also known as nicotinamide phosphoribosyltransferase, has been suggested as a pro-inflammatory and immunomodulating marker for periodontitis. The aim of this study was an immunohistochemical analysis of visfatin in gingival tissues of patients with chronic periodontitis and aggressive periodontitis.Materials and Methods:In this cross-sectional study based on clinical evaluation and inclusion and exclusion criteria. Twenty patients with generalized chronic periodontitis, 13 patients with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…Elevated visfatin expression has been observed in inflamed gingival tissues in both humans and mice [ 15 ]. Immunohistochemical staining revealed higher levels of visfatin in aggressive and chronic periodontitis gingival tissues compared to healthy gingival tissues, with no difference between aggressive and chronic periodontitis groups [ 35 ]. Visfatin expression was significantly higher in gingival tissues of periodontitis patients compared to those of healthy individuals, suggesting that local synthesis of visfatin in inflamed gingival tissues may contribute to increased visfatin levels in gingival tissues and serum [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated visfatin expression has been observed in inflamed gingival tissues in both humans and mice [ 15 ]. Immunohistochemical staining revealed higher levels of visfatin in aggressive and chronic periodontitis gingival tissues compared to healthy gingival tissues, with no difference between aggressive and chronic periodontitis groups [ 35 ]. Visfatin expression was significantly higher in gingival tissues of periodontitis patients compared to those of healthy individuals, suggesting that local synthesis of visfatin in inflamed gingival tissues may contribute to increased visfatin levels in gingival tissues and serum [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution sites of visfatin expression in gingival tissues vary across different periodontal conditions. Studies have shown that visfatin is strongly expressed in all layers of gingival tissue in patients with periodontitis, with diffuse distribution in the epithelial layer and expression in fibroblasts, endothelial cells, and intercellular matrix in the connective tissue layer [ 35 , 36 ]. In healthy gingiva, visfatin is mainly limited to the basal and parabasal layers of the epithelium, with lower intensity elsewhere and weak or no expression in the connective tissue layer [ 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In AgP patients, visfatin expression was increased in gingival tissues suggesting it might have a role in etiopathogenesis. 50 Similarly, macrophages from localized AgP patients had lower Maresin 1 (MaR1) levels (87.8 ± 50 pg/106 cells) compared to healthy controls (239.1 ± 32 pg/106 cells). As a result, phagocytosis against P. gingivalis and A. actinomycetemcomitans was reduced to 40% and neutrophils displayed slower kinetics down to 30%.…”
Section: Pathophysiologymentioning
confidence: 96%
“…Finally, sixteen studies [16,17,19,[24][25][26][27][28][29][30][31][32][33][34][35][36] were included in the meta-analysis. Seventeen studies that were impossible to include in the meta-analysis are presented in S2 Table with details and reasons [14,15,18,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] and can be considered as qualitative data. In most studies, periodontal diseases were classified based on the 1999 classification for periodontal diseases and conditions [51] and 4 studies [34,[47][48][49] based on the 2018 classification [52].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…In general, visfatin expression increases in inflammatory conditions [13]. In periodontal diseases as an inflammatory condition, an increase in visfatin levels in saliva, serum, gingival crevicular fluid (GCF) and gum tissue has been reported in various studies [14][15][16][17][18][19]. According to the results of these studies, visfatin can be used as an inflammation biomarker in periodontal diseases [16,20,21].…”
Section: Introductionmentioning
confidence: 97%